A flood tide of systematic reviews on endodontic posts: methodological assessment using of R-AMSTAR - Schmitter, Marc; Sterzenbach, G.; Faggion, C. M.; Krastl, G. (Clinical oral investigations, 2013)
To help the dental practitioner solve a specific clinical problem, systematic reviews (SRs) are seen as the best guide. In addition to the unmanageable quantity of SRs, however, one should be aware of their variable quality. The present review describes the methodological quality of SRs on postendodontic restorations to work out the value of these reviews for the dental practitioner.
Gesehen am 12.07.2021